Search
Ask a question
0

f(x) = xsquared + 2x + 5 and g(x) = x-1 then f(g)(x)

f(x) =

 

1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Roman C. | Masters of Education Graduate with Mathematics ExpertiseMasters of Education Graduate with Mathe...
4.9 4.9 (250 lesson ratings) (250)
1

You gave

f(x) = x2 + 2x + 5

g(x) = x - 1

To get f(g(x)) you just need to replace every x with g(x) in the formula for f(x) and then simplify.

In this case you would get

f(g(x)) = g(x)2 + 2g(x) + 5

            = (x - 1)2 + 2(x - 1) + 5

            = x2 - 2x + 1 + 2x - 2 + 5

            = x+ 4